Psychogenic non-epileptic seizures in youth: Individual and family psychiatric characteristics - Doss, Julia (Frontiers in Psychiatry, 2022)
Introduction: Youth with psychogenic non-epileptic seizures (PNES) are an understudied group associated with significant medical and psychiatric morbidity. Several studies have examined characteristics associated with youth’s development of this disorder, though the exploration of family factors including psychiatric illness, has been lacking. This study sought to establish the need for a more comprehensive future study. Methods: A retrospective chart review was conducted on patients who had been admitted and diagnosed with PNES at the epilepsy monitoring unit at Children’s Hospitals and Clinics of Minnesota. A total of 62 patients were included. All patients were evaluated by an epileptologist and psychologist during their diagnostic admission. “Spells” in question were captured via video EEG monitoring. PNES youth and family risk factors were assessed. Results: Mean age of PNES symptom onset was 13.9 years. Patients (73%) were diagnosed within 6 months of onset of symptoms. Histories of other impairing somatic complaints were present in the youth(54%), with 67% having prior psychiatric diagnoses. Experiencing suicidal ideation or thoughts of self-harm occurred in 47% of this sample. Family members were unaware of the history of these symptoms with 12% of the parent’s reporting awareness. Family history of psychiatric disorders (first-degree relatives of patient) was present in 54% of the sample, with anxiety, depression and conversion disorder being the most commonly endorsed diagnoses. Conclusions: Youth with PNES present with comorbid psychiatric disorders, though prior assessment and treatment for these disorders was not common. Youth with PNES have history of suicidal ideation and thoughts of self-harm, though parental awareness of these co-occurring symptoms is limited. Family risk factors, such as history of psychiatric disorder in first degree relatives, was high. The impact of these family risk factors is understudied and should be further evaluated to better understand the impact on development and maintenance of this disorder in youth.